Conceptual basis of sports training system increase effectiveness among qualified sportsmen - Anisimova, E. A.; Nazarenko, L. D. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. Competitive activity effectiveness increase among highly-qualified sportsmen is a difficult problem, which attracts attention of the experienced trainers and creatively thinking sportsmen. Special literature analysis shows that further attempts of speed-power qualities development, the search for the ways of an optimal ratio of the volume and intensity of the training load, volitional potential realization don`t give the desired effect. It was one of the reasons why sportsmen started to use pharmacological means, which activate kinesiological potential. At the same time specialists in psychology, biomechanics, theory of sports training, philosophy, pedagogics, consider that not all ways of intellectual and motional abilities of sportsmen increase are used. Material. The practice of world sport shows that in different conditions of competitive activity, the athletes with the same level of functional state, psychological, physical and technical readiness show different results. It is obvious, that till now the abilities of a man`s organism, which provide sports results increase, haven`t been studied enough.Research methods: scientific and scientific-methodical literature analysis and systematization, pedagogical experiment, testing, statistical data manipulation. Results. The article reveals the importance of theoretical training by means of deeper realization of the main methodological approaches: system, personality-oriented, culturological, synergic, the use of which provides inner processes activation, intellectual and motional activity stimulation and it helps to leave the bounds of usual notions of the training process organization. Theoretical training includes a wide variety of questions, the solution of which helps to improve the system of sports training, providing high sports results. Conclusion. Pedagogical experiment results showed, that a sportsman` s intellect activation, the analysis use of the accumulated subjective experience, appearing feelings and specific senses set athletes to the search for self-development ways, the ways of natural potential realization for a planned result achievement.